A PRELIMINARY STUDY OF RESOURCE MANAGEMENT IN A HIGHER EDUCATIONAL INSTITUTION (FUDMA JOURNAL OF SCIENCES, 2025)
In today's organizational landscape, Information and Communication Technology (ICT) plays a pivotal role in enhancing operational efficiency and facilitating rapid decision-making processes. The extent of ICT investment and implementation has emerged as a critical determinant of organizational success, particularly in the post-COVID-19 era. The shift towards remote operations and processes, driven by COVID-19 protocols, has underscored the importance of ICT devices and tools in ensuring organizational success, regardless of size. This research examines the workplace limitations of human resource management within a higher educational institution. Specifically, it investigates job roles and the utilization of computers in achieving organizational objectives. The findings reveal significant inefficiencies stemming from misalignment between staff job roles and their training, leading to underutilization of their skills and potentials. This paper presents preliminary study highlighting the workplace limitations of human resources in higher educational institutions, emphasizing the need for strategic realignment and utilization of human capital to optimize organizational performance.
Keywords: Decision Support System (DSS); Institutional Repository; Resource Management; Organizational Resources; Lockdown